THE USE OF LIME IN THE TREATMENT OF ENVIRNOMENTAL PROBLEMS - Τριαντάφυλλου Γ.; Μανούτσογλου Ε. (Bulletin of the Geological Society of Greece, 2004)
Lime is a product with several uses. The most important are in metallurgy, in the manufacture of paper, glass, paints and sugar, for construction and environmental uses. At the present study the contribution of lime in the protection of environment is described. The lime industry product constitutes a significant segment of the environment industry with future prospects of growth. The treatment of municipal potable water, the treatment of urban sewages, the contribution in the neutralization of acid industrial discharges and the flue gas desulfurization, constitute the main environmental applications of the lime industry products. It is appreciated that the continuously increasing demand of products and technologies friendly to the environment over the next decade will have as a consequence the increase of lime production, particularly after the increasing application of stricter environmental legislation in national, as well as in global level.